Effect of Lecithin Addition and Conching Time on the Physicochemical Quality of Milk Chocolate Couverture - Andriani, Revina Catharina; Ulya Sarofa; Luqman Agung Wicaksono (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Couverture chocolate is a type of chocolate that uses a high percentage of cocoa butter to produce a better flavor. The method used was a completely randomized design (CRD) factorial pattern with two factors and two replicates. Factor I was lecithin concentration (0.5%; 0.7%; and 0.9%), and factor II was conching time (20 hours, 24 hours, and 28 hours). Data were analyzed using ANOVA and DMRT further test at the 5% level. The results of the study with the best treatment were obtained in the treatment combination of 0.9% lecithin concentration with a conching time of 28 hours which produced Milk Chocolate Couverture with a moisture content of 1.24%, fat content of 39.46%, melting point of 38oC, hardness 2.3 N, cohesiveness 0, 28, springiness 1.22 mm, gumminess 37.50 g, chewiness 0.22 mJ, color test (L* value 38.60, a* value 15.51 and b* value 47.66) and organoleptic test which includes color quality attributes 3.88 (neutral-like), aroma 3.76 (neutral-like), taste 4.04 (like) and texture 4.20 (like). Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production